Campomanesia lineatifolia Ruiz e Pav.: estudo fitoquímico e avaliação da atividade antioxidante - Jamile Barbosa (2009)
Campomanesia lineatifolia Ruiz & Pav. is a fruit tree belonging to the Myrtaceae Jussieu family, popularly known in Brazil as gabiroba or guabirabeira. Its native form can be found in the western Amazonia. The leaves and stem bark of Campomanesia species are popularly used as a healing agent or in the treatment of diarrhea and gastric ulcer. It was researched the major special metabolites of Campomanesia lineatifolia and was evaluated its potential in vitro antioxidant activity, related to their traditional uses. Leaf powder was submitted to percolation in ethanol and the obtained crude extract was pre-purified by liquid-liquid partition in immiscible solvents with increasing polarities, wich originated four fractions: Hex. Fr., CH Fr., EtOAc Fr. and BuOH Fr. The EtOAc fraction, wich showed the best antioxidant activity, was fractionated using high-speed countercurrent chromatography (HSCCC) and reversed-phase high performance liquid chromatography (RP-HPLC). This fractionation resulted in the isolation of three substances. Two of them were identified by spectroscopic techniques as catechin and quercitrin. The crude ethanolic extract and the fractions, as well as the isolated substances catechin and quercitrin, were submitted to four in vitro antioxidant activity tests: TEAC (Trolox Equivalent Antioxidant Capacity); DPPH (2,2-Diphenyl-1-picrylhydrazyl/Free Radicals Sequestrant); Antioxidant Capacity (Phosphomolybdenum method); Reducing Power (Ferricyanide method/Prussian Blue). The total phenols, tannins and flavonoids were determined in the leaf powder, crude extract and obtained fractions. C. lineatifolia is rich in phenols, with large amount of tannins (»18% for crude extract) and flavonoids (»9% for EtOAc Fr.). The crude ethanolic extract shown antioxidant activity in all performed tests and the best results were achieved in the BuOH Fr. and AcOEt Fr. Their DPPH test showed a EC of 10.02±0.05 and 6.83±0.04 µg/mL and the TEAC assay 1.69±0.10 and 1.36±0.10, respectively. So, is suggested that high polyphenols concentration in C. lineatifolia extract and fractions and the antioxidant activity are closely related to their ethnopharmacological uses. Key-words: Campomanesia lineatifolia, Myrtaceae, gabiroba, in vitro antioxidant activity, DPPH, TEAC.